2008
DOI: 10.2105/ajph.2007.120915
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health in Sumatra After the Tsunami

Abstract:  RESEARCH AND PRACTICE  Objectives. We assessed the levels and correlates of posttraumatic stress reactivity (PTSR) of more than 20 000 adult tsunami survivors by analyzing survey data from coastal Aceh and North Sumatra, Indonesia.Methods. A population-representative sample of individuals interviewed before the tsunami was traced in 2005 to 2006. We constructed 2 scales measuring PTSR by using 7 symptom items from the Post Traumatic Stress Disorder (PTSD) Checklist-Civilian Version. One scale measured PTSR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
85
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(91 citation statements)
references
References 19 publications
6
85
0
Order By: Relevance
“…However, recent papers have examined the impact of natural disasters on outcomes such as macroeconomic output (Noy, 2009), income and international financial flows (Yang, 2008a), migration decisions (Halliday, 2006;Paxson and Rouse, 2008; Yang, 2008b), fertility and education investments (Baez et al, 2010;Finlay, 2009;Portner, 2008;Yamauchi et al, 2009), and even mental health (Frankenberg et al, 2008). To our knowledge this is the first paper which attempts to examine the effect of natural disasters on risk-taking behavior in a developing country.…”
Section: Cyclones (Ipcc 2001)mentioning
confidence: 99%
“…However, recent papers have examined the impact of natural disasters on outcomes such as macroeconomic output (Noy, 2009), income and international financial flows (Yang, 2008a), migration decisions (Halliday, 2006;Paxson and Rouse, 2008; Yang, 2008b), fertility and education investments (Baez et al, 2010;Finlay, 2009;Portner, 2008;Yamauchi et al, 2009), and even mental health (Frankenberg et al, 2008). To our knowledge this is the first paper which attempts to examine the effect of natural disasters on risk-taking behavior in a developing country.…”
Section: Cyclones (Ipcc 2001)mentioning
confidence: 99%
“…However, it is diffi cult to infer causality between the characteristics of the community and health because (a) there is an absence of an appropriate control group (those who were unexposed to the disaster) in order to draw appropriate counterfactual comparisons and (b) there is an absence of information on predisaster levels of health and variable confounders, or the use of retrospective recall, which can be biased (Buttenheim, 2010 ). A notable exception is the Study of the Tsunami Aftermath and Recovery (STAR) following the December 26, 2004, Indian Ocean tsunami (Frankenberg et al, 2008 ). In that study, residents in Indonesia had been interviewed ten months before the tsunami as part of the National Socioeconomic Survey (SUSENAS) conducted by Statistics Indonesia.…”
Section: Further Study On Disaster and Healthmentioning
confidence: 99%
“…A follow-up survey was conducted during [2005][2006], in which investigators recontacted over 25,000 individuals who had participated in the original survey. The study found that symptoms of PTSD were highest among respondents from the most heavily damaged areas and among those who suffered loss of kin and property damage (Frankenberg et al, 2008 ). There is another solution to obtaining data before a disaster.…”
Section: Further Study On Disaster and Healthmentioning
confidence: 99%
“…Frankenberg et al (2008) indicate that survivors from coastal Aceh and North Sumatra, Indonesia, which were areas damaged by the Indian Ocean Tsunami in 2004, experienced post-traumatic stress reactions (PTSR). Population-representative interview surveys were conducted both before and after the tsunami and included residents from heavily damaged and indirectly damaged areas.…”
Section: Introductionmentioning
confidence: 99%